2022
DOI: 10.3389/fneur.2022.864689
|View full text |Cite
|
Sign up to set email alerts
|

Petasites for Migraine Prevention: New Data on Mode of Action, Pharmacology and Safety. A Narrative Review

Abstract: Petasins are the pharmacologically active ingredients of butterbur and of therapeutic benefit in the treatment of migraine and tension headaches. Here, we summarize the pharmacology, safety and clinical efficacy of butterbur in the prevention of migraine attacks and present new data on its mode of action. We review published literature and study reports on the safety and clinical efficacy of the butterbur root extract Petadolex® and report new findings on petasins in dampening nociception by desensitizing calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It was determined that the root extract inhibits the release of calcitonin-generelated peptide (CGRP) of meningeal afferents during migraine attacks. In randomized, doubleblinded, and placebo-controlled trials, the root extract Petadolex® reduced the frequency of migraine attacks significantly at 150 mg/day, and no relevant abnormal liver function was reported (Borlak et al, 2022).…”
Section: Butterbur (Petasites Hybridus)mentioning
confidence: 99%
“…It was determined that the root extract inhibits the release of calcitonin-generelated peptide (CGRP) of meningeal afferents during migraine attacks. In randomized, doubleblinded, and placebo-controlled trials, the root extract Petadolex® reduced the frequency of migraine attacks significantly at 150 mg/day, and no relevant abnormal liver function was reported (Borlak et al, 2022).…”
Section: Butterbur (Petasites Hybridus)mentioning
confidence: 99%
“…Considering that CGRP, as a key peptide, plays an important role in pain signaling, it has been demonstrated that CGRP release can be inhibited using herbs ( 24 ). The transient receptor potential ankyrin (TRPA) mediates CGRP release in neurogenic inflammation, and the study by Benemei et al ( 25 ) demonstrates that Petasin inhibits CGRP signaling, achieving this through desensitization of TRPA.…”
Section: Mechanisms Of Action Of Migrainementioning
confidence: 99%
“…There was noted desensitization of nociception by acting on calcium-conducting transient receptor potential (TRP) ion channels ( selectively TRPA1 and TRPPV1) of primary sensory neurons impairing their dual function of signaling pain and releasing the neuropeptides, substance P, and calcitonin-gene related peptide (CGRP), which mediate neurogenic inflammation. [48,50] Petadolex, introduced in 1972 in Germany and 1998 in the USA, is the only one among many of butterbur extracts, whose clinical efficacy and safety were amply evaluated in the preventive treatment of migraine. [50] Adverse effects of butterbur generally are rare, mild, and well-tolerated, and include gastrointestinal upset, eructation, nausea, diarrhea, headache, dizziness, increased bleeding tendency, and rash.…”
Section: Butterburmentioning
confidence: 99%